Asset Securitizations and Credit Default Swaps. Issue 4 (November 2014) - Zhang, John Ziyang
<x xml:space="preserve">Abstract</x> This study examines the effects of off‐balance sheet versus on‐balance sheet securitizations on the originator's credit risk in the default swap (CDS) market across the recent business cycle from 2002 to 2009. I find that on‐balance sheet securitizations demonstrate greater effects on the originator's CDS premium than off‐balance sheet securitizations in the business cycle. While off‐balance sheet securitizations' effects on the originator's CDS premium become significantly stronger after 2007 when the economy declines, on‐balance sheet securitizations' effects on the originator's CDS premium do not experience a significant change with the onset of the recession. The results suggest that the CDS market views originators as having greater probabilities not to honour their implicit guarantees for off‐balance sheet securitizations during the economic downturn. The results also indicate that on balance sheet and off‐balance sheet securitizations have distinctly different risk properties. It would be beneficial to investors if regulations take into considerations the changing credit risks of off‐balance sheet securitizations and the different structures of asset securitizations.